The plague cemetery of Alghero, Sardinia (1582-1583) : the bioarchaeological study - Giuffra, Valentina, (Archaeopress Archaeology, 2022)
This study presents a bioarchaeological analysis of the individuals exhumed from the cemetery of Alghero (Sardinia), which is associated with the plague outbreak that ravaged the city in 1582-83. The results shed light on a population which lived during a period of plague, revealing lifestyles, activity patterns and illnesses.